Productive faces of shame: An interview with Elspeth Probyn. (May 2019) - Probyn, Elspeth; Bozalek, Vivienne; Shefer, Tamara; Carolissen, Ronelle
Shame has typically been understood as a negative emotion, a view which is prevalent in individualist, psychologising discourses about human experience. Elspeth Probyn's approach to shame departs significantly from these tropes. As interviewers, we share a common interest in feminist ethics and productive affects in teaching and scholarship. Hence, our specific interest in Probyn's Blush: Faces of Shame. Blush is an excellent example of viewing the politics of shame as a productive and relational process. Probyn proposes that shame comes about through an interest in and a connection with another. This connection can result in building care for the other and community through re-evaluations of the self. In this way, shame can be a productive force in postcoloniality, in the feminist political ethics of care and in attempts at reconciliation. This view corresponds with the focus of this Special Issue – an affirmative and relational but political view of shame. The interview provides an illuminative account of the author's thoughts behind the writing of the book Blush, historical, theoretical and personal influences which impacted on the ideas expressed in the book, and how the book relates to past and future ideas and practices.